1972
DOI: 10.1126/science.175.4029.1469
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromones of Summer Fruit Tortrix Moth Adoxophyes orana : Two Synergistic Isomers

Abstract: Both cis-9-and cis-11-tetradecenyl acetate were isolated from 2500 virgin females of the summer fruit tortrix moth Adoxophyes orana (F.v.R.) by gel permeation, column chromatography on silica gel, and gas chromatography. Their chemical, physical, and biological properties were identical to those of the synthetic compounds. In contrast to the single compounds, mixtures of these pheromones were highly active in laboratory and field tests. Catches, in traps, with the pheromone mixture were comparable to those obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

1973
1973
1979
1979

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 17 publications
0
27
0
2
Order By: Relevance
“…Amoeboid cells crawl parallel to a d-c electric field toward the cathode at only a few volts per centimeter (1). Mast reported that Amoeba proteus extended pseudopodia perpendicular to a 60-hz a-c electric field (2).…”
Section: A Second Active Fraction (Not Yet Analyzed)mentioning
confidence: 99%
“…Amoeboid cells crawl parallel to a d-c electric field toward the cathode at only a few volts per centimeter (1). Mast reported that Amoeba proteus extended pseudopodia perpendicular to a 60-hz a-c electric field (2).…”
Section: A Second Active Fraction (Not Yet Analyzed)mentioning
confidence: 99%
“…Acetylation of 27 in 0.5 n~l product formation the a b s o l~~t e loading of aldehyde on of acetic anhydride and 5 ml of pyridine gave an oil, the polymer could not be determined, but could obviously which on purification by preparative tlc (eluant ethernot be more than the polymer-bound diol, and is likely benzene 2:3), yielded 48 mg (0.19 mmol) of pure ISabout 60% of the loaded diol value. tetradecen-1-01 acetate (20,36) (30) in high yield (Table 1).…”
Section: Preparation Of Diol Monomeg~lafes 11-13mentioning
confidence: 99%
“…
7 were oxidized with the Sharpless reagent (CrO,Cl,/tert-butyl alcohol/pyridine) to give polymer-bound aldehydes [35][36][37], which on reaction with Wittig reagents and subsequent hydrolysis and acetylation gave 28, 29, and 10-tetradecen-1-01 acetate (47)
…”
mentioning
confidence: 99%
“…The smaller tea tortrix (STT) and the summer-fruit tortrix (SFT) occur sympatrically in Japan (272}and their mating times are not significantly different under laboratory conditions (273). The sex pheromones of the two species have been identified as mixtures of (Z)-9-and (Z)-ll-tetradecenyl acetate (274)(275)(276)(277), yet field trapping experiments with virgin females and mate-choice experiments in the laboratory clearly indicate a significant sexual isolation (278). The ratio of Z9-l4: Ac to Zl1-l4: Ac is 63: 37 in STT and 82: 18 in SFT (273) and the ability of males to discriminate between these ratios to a slight extent was demonstrated (273).…”
Section: A Geometric Isomersmentioning
confidence: 99%